Species distribution and molecular variations in drogonflies (order: odonata) within the state of Selangor, Malaysia / Noorhidayah Binti Mamat - Noorhidayah, Mamat (2013)
Dragonflies have been used in an extensive array of studies dealing with the functional morphology, behavior, ecology, and evolution. They have been indicated to be important in functioning as bioindicators. The major aim of this study is to investigate the dragonfly population in the Selangor areas and to conduct the analysis on the molecular systematic and phylogenetics. Field sampling was done in 22 sites for the odonate biodiversity studies and the mitochondrial gene – partial regions of NADH dehydrogenase subunit 1 (ND1) was utilized for the molecular aspects. The results revealed a total of 1298 individuals belonging to 54 species from 9 families of Odonata which showed a significant preference for tropical lowland rainforest (TLR) in contrast to the open areas (OP). This was supported by the higher indices of richness (R) diversity (H’) and evenness (E) for TLR. The phylogenetic trees were constructed from 40 samples using the neighbor joining (NJ) and maximum parsimony (MP) algorithms which were implemented by MEGA 4.0.2. One consistent result across all the analyses was the Suborder Anisoptera as a monopyletic group. Opposite to suborder Zygoptera, they were resolved clustered into 2 clusters, paraphyletic group. The distinct separation between cluster Anisoptera and Zygoptera with confidence level 72% in the NJ analyses while 90% in MP analyses. It is suggested that ND1 gene sequences can serve as a reference for DNA-based identification purposes, especially when in doubt for the larvae identification. The population aspects provided a baseline information for the future monitoring of Odonata in the Selangor areas related to diversity, abundance, distribution as well as the effects of physical parameter of the study sites.